2004
DOI: 10.1186/cc2983
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular stability during arteriovenous extracorporeal therapy: a randomized controlled study in lambs with acute lung injury

Abstract: Introduction Clinical application of arteriovenous (AV) extracorporeal membrane oxygenation (ECMO) requires assessment of cardiovascular ability to respond adequately to the presence of an AV shunt in the face of acute lung injury (ALI). This ability may be age dependent and vary with the experimental model. We studied cardiovascular stability in a lamb model of severe ALI, comparing conventional mechanical ventilation (CMV) with AV-ECMO therapy. Methods Seventeen lambs were anesthetized, tracheotomized, paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Inhalational anesthesia was used in two studies [ 16 , 19 ]. Only four studies reported a protocolized approach to cardiovascular support [ 12 , 24 , 25 , 27 ], while six studies provided data on cumulative fluid balance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhalational anesthesia was used in two studies [ 16 , 19 ]. Only four studies reported a protocolized approach to cardiovascular support [ 12 , 24 , 25 , 27 ], while six studies provided data on cumulative fluid balance.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli LPS over 30 mins Not stated Hou et al [ 17 ] Hypoxia (discontinuation of mechanical ventilation) Not stated Langer et al [ 22 ] 0.1–0.15 mL/kg i.v. OA P/F < 200 mmHg Shekar et al [ 14 ] Smoke inhalation (10–12 mL/kg Vt breaths of cotton smoke, first cycle 12 breaths, then cycles of 8 breaths) repeated until injury achieved Carboxyhemaglobin 45–50% Totapally et al [ 27 ] Saline lavage (mL/kg) repeated × 3 and 2.5 mL/kg i.t. 0.1 N HCL Not stated Germann et al [ 15 ] 0.5 mL/kg i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os três desvios cardiopulmonares possíveis para a ECMO, veno-venoso, venoarterial e artério-venoso, este último envolve menos complicações operacionais do que os demais (TOTAPALLY et al, 2004), já que, fora o suprimento de oxigênio, o sistema não requer fontes adicionais de energia, como a máquina de circulação extracorpórea (ZIMMERMANN et al, 2007). É o gradiente de pressão sanguínea que impulsiona o sangue através do circuito (KOPP et al, 2006), sendo o coração a bomba pressora.…”
Section: Introductionunclassified